ПРИМЕНЕНИЕ МУКОАКТИВНЫХ ЛЕКАРСТВЕННЫХ СРЕДСТВ В ПРАКТИКЕ ТЕРАПЕВТА - Ф. Т. Малыхин; А. А. Визель; И. Ю. Визель (SINAPS LLC, 2013)
Russia is among the countries where using of mucolytic drugs in clinical practice is widespread. In chronic bronchitis, chronic obstructive pulmonary disease, acute respiratory syndrome with prolonged cough, pneumonia, tuberculosis and many other pathologies using of expectorants and mucoregulating drugs is common. Among the synthetic mucolytics benzyalamine bromhexine has been introduced for a long time in practice; and then its derivative - ambroxol hydrochloride which has better pharmacokinetics and pharmacodynamics. Using of ambroxol (Ambrobene) in patients with cough, accompanied by difficult expectoration, is useful as it promotes the implementation of the protective cough reflex, providing evacuation of viscous mucus or foreign particles from the respiratory tract.